Efficiency improvement of planar perovskite solar cells using a phenol additive. Issue 43 (30th October 2018) - Fu, Jiehao; Sun, Kuan; Yang, Ke; Hu, Lijun; Leng, Chongqian; Kan, Zhipeng; Duan, Tainan; Li, Meng; Shi, Haofei; Xiao, Zeyun; Lu, Shirong; Ouyang, Jianyong
Abstract : Phenol is introduced as a less-stringent solvent additive to improve the efficiency of perovskite solar cells. Abstract : Phenol is introduced as a solvent additive in the perovskite precursor solution. In a wide concentration range between 5 and 75 mg ml −1, it can improve the quality of active layers by decreasing the concentration of defect states, leading to a 20% enhancement in perovskite solar cell performance. O–Pb coordination and complete removal of the additive contribute to the high quality of the perovskite film.